Equitable distribution of low-cost houses in Malaysia: constraints and challenges - Sufian, Azlinor; Ibrahim, Ahmad (Faculty of Economics and Management, Universiti Putra Malaysia, 2011)
The government policies on low-cost housing have transpired from various Malaysian Plans. According to the Tenth Malaysia Plan, continuous efforts will be put into ensuring Malaysian citizens from all level of income to have opportunity to acquire houses that are normally referred to as “adequate, affordable and good quality.” Since issue of housing is more crucial in urban areas, greater emphasis is placed on the low-income group for better urban services and healthy living.(Government of Malaysia, 2010) A study on all Malaysian Plans have shown that the government encourages the private sector to build more low-cost houses and low-medium-cost houses. On the other hand the public sector concentrates on providing houses for lower income group and houses for public sector employees. Despite deep involvement of both public and private sectors in providing low-cost houses to the low-income group, there is still a problem of inadequate supply of low-cost units. This article examine the Open Registration System (“ORS”) established by the Ministry of Housing and Local Government of Malaysia (“MHLG”) in registration of intended purchasers and distribution of low-cost houses to the targeted groups that is the low-income group, identify the constraints and challenges in implementing the system and make suggestions for reforms in terms of legal and institutional frameworks within Peninsula Malaysia